If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(t-3)+4=4(2t-4)
We move all terms to the left:
4(t-3)+4-(4(2t-4))=0
We multiply parentheses
4t-(4(2t-4))-12+4=0
We calculate terms in parentheses: -(4(2t-4)), so:We add all the numbers together, and all the variables
4(2t-4)
We multiply parentheses
8t-16
Back to the equation:
-(8t-16)
4t-(8t-16)-8=0
We get rid of parentheses
4t-8t+16-8=0
We add all the numbers together, and all the variables
-4t+8=0
We move all terms containing t to the left, all other terms to the right
-4t=-8
t=-8/-4
t=+2
| 4x2+3=−3x | | -2(n+3)-1=-1+n | | -2(n+3)-1=-1 | | 6(x-2)/2=3(x+9)/2 | | ¼y=-4½ | | 3n+40=61 | | 27=x/4+8 | | 19.48+y=37.48 | | x-3(3+3x)=-9-2x | | -17x+170/x+11=0 | | 14+x=3(3x+2) | | ^2+12x=-25 | | y-8/2=9 | | -6+2m=-3(3m+2) | | 7z−4=52 | | 9(5y=36) | | 16x-14=9x-7 | | 5x-3(1-7x)=205 | | 3(x+4)+2=6x-3(-4+x) | | 5t-5=9t+5 | | -4(-5r+2)+1=-107 | | (6x+3)+(7x-19)=180 | | 7(5+7x)-4=-263 | | -2(5p+8)=-86 | | 6x-3(x+7)=x+51 | | 5x-2=3×-8 | | 1/2m-3/4=16 | | 5x+6=2x+4x | | 5(2n+1)=8(5n+1)+5 | | x+4(–3x+4)=–6 | | 15x(2+4)=34 | | n/0.5=0.02/5 |